Assistance in Processing Household Plastic Waste into Ecobricks at Medas Harmony Housing, West Lombok - Suwati Ummat; Marianah Marianah; Muanah Muanah; Ahmad Akromul Huda; Desy Ambar Sari; Budy Wiryono (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2021)
Household waste contributes to the volume of waste. In general, household waste is easily biodegradable and difficult to decompose. Household products that are hard to decompose are generally plastic and plastic bottles predominantly. The difficulty of decomposing household plastic waste requires serious handling, so it is necessary to provide assistance for processing plastic waste into useful creations. One of them becomes ecobric. There are two methods of this activity, namely direct counseling and training. The results obtained after the community service activities were completed was that they were able to improve community skills in processing plastic waste into ecobrics. Furthermore, ecobrics are created into potted plants and other forms of creation. In addition, after this activity is carried out, it can reduce the movement of plastic waste to the final disposal site (TPA), so that the community hopes that this activity will continue to be transmitted to other places to create a clean and free environment from plastic waste.